Desarrollo de una aplicación web para el análisis de precios de alojamientos turísticos de la provincia de Cotopaxi empleando técnicas de web scraping. - Gomez Avalos, Alex Roberto (2023)
A web application development is stood out for the analysis of tourist accommodation prices in the Cotopaxi province, using web scraping techniques. Tourism is a constantly growing industry and is essential to have tools that allow users to access and compare accommodation prices quickly and efficiently. The developed web application focuses on extracting data from multiple tourist accommodation reservation websites in the Cotopaxi province using web scraping techniques. These techniques make it possible to automate the information extraction in a systematic and precise manner. Once the data is extracted, the processing and analysis is carried out to obtain relevant statistics, such as average prices by type, location and season accommodation. The web application offers an intuitive and friendly interface for users, who can filter and search for accommodation according to their preferences and needs. In addition, data visualization functions, such as graphs and tables, are included to facilitate the results interpretation. Developing this web application has several advantages. First, it provides users with an accessible and easy-to-use tool to obtain updated information on tourist accommodation prices in the Cotopaxi province. This allows them to make informed decisions when planning their trips and optimizing their budget. In addition, the web application can be a valuable tool for the owners of tourist accommodation, since allows them to monitor and compare their prices with those competition. This will help them adjust their pricing strategies and stay competitive in the market.